AFM PeakForce QNM mode: Evidencing nanometre-scale mechanical properties of chitin-silica hybrid nanocomposites. (20th October 2016) - Smolyakov, G.; Pruvost, S.; Cardoso, L.; Alonso, B.; Belamie, E.; Duchet-Rumeau, J.
Highlights: The mechanical properties of chitin-silica hydrid nanocomposites are probed at the nanoscale. The determination of DMT modulus by AFM in QNM mode is affected by the applied force. The presence of excess silica induces mechanical strengthening at the interface. Stress is transferred from the hard silica phase to the softer chitin nanorods. Abstract: PeakForce Quantitative Nanomechanical Mapping (QNM) AFM mode was used to explore the mechanical properties of textured chitin-silica hybrid films at the nanoscale. The influence of the force applied by the tip on the sample surface was studied for standard homogeneous samples, for chitin nanorods and for chitin-silica hybrid nanocomposites. Thick films of superimposed chitin nanorods showed a monotonous increase of DMT modulus (based on the Derjaguin-Muller-Toporov model) owing to an increase in modulus at the interface between nanorods due to geometrical constraints of the AFM acquisition. A similar variation of DMT modulus was obtained for chitin-silica hybrid thick films related to mechanical strengthening induced by the presence of silica. This work revealed the role of the organic-inorganic interface, at the nanoscale, in the mechanical behaviour of textured materials using PeakForce QNM mode, with optimized analysis conditions.